Imaging Approaches for Dementia - Murray, A.D. (American Journal of Neuroradiology, 2012)
SUMMARY: Brain imaging has progressed from exclusion of rare treatable mass lesions to a specific antemortem diagnosis. MR imaging−derived hippocampal atrophy and WMH are regarded as imaging biomarkers of AD and CVD respectively. Abnormal FP-CIT SPECT or cardiac iodobenzamide SPECT is a useful supportive imaging feature in the diagnosis of DLB. Frontal and/or anterior temporal atrophy and anterior defects on molecular imaging with FDG-PET or perfusion SPECT are characteristic of FTDs. Whole-body FDG-PET may be helpful in patients with rapidly progressing “autoimmune dementias,” and FLAIR and DWI are indicated in suspected CJD. A major role of imaging is in the development of new drugs and less costly biomarkers. apoEapolipoprotein EAPPamyloid precursor proteinbvFTDbehavior variant frontotemporal dementiaCJDCreutzfeldt-Jacob diseaseCVDcerebrovascular diseaseDLBdementia with Lewy bodiesFP-CITiodine-123-β-carbomethoxy-3 β-(4-iodophenyltropane) fluoropropylFTDfrontotemporal dementiaMCImild cognitive impairmentPDParkinson diseaserCBFregional cerebral blood flowsCJDsporadic Creutzfeldt-Jacob diseaseTDPTAR deoxyribonucleic acid−binding protein 43VBMvoxel-based morphometryvCJDvariant Creutzfeldt-Jacob diseaseWMHwhite matter hyperintensities